How far away is an intangible? Services FDI and distance - Ronald B. Davies; Amélie Guillin (University College Dublin, UCD School of Economics, 2011)
Foreign direct investment (FDI) in services has grown significantly in recent years. Evidence of spatial relationships in FDI decisions have been provided for goods manufacturing by utilizing physical distance-based measures of trade costs. This paper investigates spatial interactions for services FDI using several distance measures, including physical distance, genetic distance, and transport time. Across different measures of distance, the traditional determinants of outbound FDI activity remain valid for services. We also find spatial interdependence for services FDI that is generally supportive of complex vertical motivations.
Keywords: F21; F23; 330; Foreign direct investment; Services; Spatial econometric techniques